Stochastic Hybrid Hepatitis B Epidemic Model with Markovian Switching. (23rd May 2022) - El Koufi, A.; Seshagiri Rao, N.
Abstract : In this paper, we consider a stochastic epidemic model under regime-switching. We show that our model is well-posed by proving the existence of solution, positivity, and uniqueness. Furthermore, we investigate sufficient conditions for the existence of ergodic stationary distribution to the model, which shows that the hepatitis B epidemic will persist. In addition, we establish sufficient conditions for the extinction of the hepatitis B epidemic. We perform numerical simulations to confirm and illustrate the theoretical results.